IDENTIFIKASI TANDA TANGAN DENGAN DETEKSI TEPI DAN KOEFISIEN KORELASI - Santoso, Harry (Universitas Katolik Soegijapranata, 2017)
Signature is a proof of identity of a person that is used for verification and authentication. The existence of a signature in a document is important to indicate its validity. This project intends to detect the level of similarity between two signature images by using correlation coefficient. The signature image will be processed through two stages namely preprocessing and identification. Preprocessing consists of grayscaling, filtering, sharpening, tresholding, and edge detection. This stage results a black and white image with signature pattern in white. The identification stage is done by calculating correlation coefficient value of the input image and each database image.